Politics and Power in the Record Industry: The Beatles, the Beach Boys, and the Album as Art Form. Issue 2 (2nd July 2016) - Harvey, Mark
Abstract : The album as an art form emerged in the mid-1960s, in part because rock musicians demanded greater studio autonomy from record companies. However, an underexplored factor contributing to the emergence of the art rock album is how record companies began to market their 'stars' as 'artists' as a means to sell more records. This article focuses upon how Capitol Records capitalized upon the artistry of the Beatles and the Beach Boys to change the norms of the industry, leading to the increased marketability of the album as a coherent work of art.